2016
DOI: 10.1016/j.jenvman.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Nest-site competition between invasive and native cavity nesting birds and its implication for conservation

Abstract: Nesting cavities are often a limited resource that multiple species use. There is an ongoing discussion on whether invasive cavity nesting birds restrict the availability of this key limited resource. While the answer to this question has important conservation implications, little experimental work has been done to examine it. Here, we aimed to experimentally test whether alien cavity nesting birds affect the occupancy of cavities and the resulting breeding success of native cavity breeders in a large urban p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 42 publications
1
40
1
Order By: Relevance
“…For example, long-term monitoring of bat boxes in Melbourne, Australia has shown that, despite the provision of boxes constructed from materials with a range of insulative properties (ranging from 12 mm plywood to 90 mm pine), box use was dominated by one widespread, urban-adapted species, Gould's wattled bat Chalinolobus gouldii (Gray, 1841) [71]. Further research is required to investigate whether there is a link between the thermal profiles in nest boxes (compared to tree hollows) deployed in disturbed landscapes and their disproportionate level of use by widespread, highly adaptable species of birds [29,93,94] and mammals [21,71,95,96]. Field-based studies examining rates of occupation of chainsaw hollows and log hollows by target species versus undesirable exotic species would be of great interest, particularly in urban and peri-urban landscapes where nest box programs are often undertaken by land managers and conservation-focused community groups [4,97].…”
Section: Discussionmentioning
confidence: 99%
“…For example, long-term monitoring of bat boxes in Melbourne, Australia has shown that, despite the provision of boxes constructed from materials with a range of insulative properties (ranging from 12 mm plywood to 90 mm pine), box use was dominated by one widespread, urban-adapted species, Gould's wattled bat Chalinolobus gouldii (Gray, 1841) [71]. Further research is required to investigate whether there is a link between the thermal profiles in nest boxes (compared to tree hollows) deployed in disturbed landscapes and their disproportionate level of use by widespread, highly adaptable species of birds [29,93,94] and mammals [21,71,95,96]. Field-based studies examining rates of occupation of chainsaw hollows and log hollows by target species versus undesirable exotic species would be of great interest, particularly in urban and peri-urban landscapes where nest box programs are often undertaken by land managers and conservation-focused community groups [4,97].…”
Section: Discussionmentioning
confidence: 99%
“…These activities may include a variety of active and passive management actions targeting non‐native species, such as trapping and euthanasia, removing nests or eggs, shooting adults, or modifying the nest box (Larson et al, ). We define active management as lethal techniques such as euthanizing birds (Grarock, Tidemann, Wood, & Lindenmayer, ; Weitzel, ), removing nests or eggs, oiling or addling eggs (Fernandez‐Duque, Bailey, & Bonter, ; Hindman, Harvey, & Conley, ), and we define passive management as nonlethal techniques, such as reducing entrance hole sizes to exclude unwanted species based on body size (Charter, Izhaki, Ben Mocha, & Kark, ). Invasive bird management is legal (i.e., no permit necessary) under the Migratory Bird Treaty Act of 1918 in the United States and the Migratory Birds Convention Act of 1994 of Canada, both of which only protect species native to North America.…”
Section: Introductionmentioning
confidence: 99%
“…For passerine birds, especially those species that are secondary cavity nesting, nest sites are crucial aspects of their life histories; competition for nest sites must be severe, because (a) such species build nests in cavities as places for incubating their eggs and rearing their offspring, and (b) they cannot excavate cavities by themselves, but instead search for ready‐made holes that are generally limiting resources in nature. Although previous studies have demonstrated some nest site competition within or among birds, most of those studies focused on the conservation issue due to nest competition between introduced and native species (Charter, Izhaki, Ben Mocha, & Kark, ; Heinsohn, Murphy, & Legge, ; Hernandez‐Brito, Carrete, Ibanez, Juste, & Tella, ; Ingold, ; Kerpez & Smith, ).Very few studies have investigated the effect of nest‐site competition on habitat overlap (Minot & Perrins, ).…”
Section: Introductionmentioning
confidence: 99%